Preferensi Strategi Pemasaran Bank Syari’ah Menanggapi Perilaku Konsumsi Masyarakat Saat Musim Panen - Rendra Anjaswara; H Hardivizon (Institut Agama Islam Negeri (IAIN) Curup, 2017)
Consumption behavior that shown by the community during the harvest season has not aroused awareness of sharia banks to implement special marketing strategies in response to the phenomenon. This research is a field research with qualitative approach. The location of this research is in DusunSawah,North Curup District, RejangLebongRegency with the consideration of the number of people who work as farmers and the extent of agricultural land and plantations. The results showed that the consumption behavior of farmers in DusunSawah is consumptive during the harvest season. Consumptive behavior is influenced by three dominant factors, namely cultural factors, social factors, and personal factors. Therefore, the preference of marketing strategies that can be applied by sharia banks in response to consumptive behavior of farmer society ofDusun Sawah in harvest season is concentrated marketing strategy with the concept of event marketing and coffee break marketing.